2019
DOI: 10.1186/s12887-019-1661-x
|View full text |Cite|
|
Sign up to set email alerts
|

Breastfeeding and timing of pubertal onset in girls: a multiethnic population-based prospective cohort study

Abstract: Background Early puberty is associated with higher risk of adverse health and behavioral outcomes throughout adolescence and adulthood. US girls are experiencing earlier puberty with substantial racial/ethnic differences. We examined the association between breastfeeding and pubertal timing to identify modifiable risk factors of early puberty and potential sources of racial/ethnic differences in the timing of pubertal development. Methods A prospective cohort study of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 36 publications
2
24
0
1
Order By: Relevance
“…Our study also found breastfeeding as a possible protective factor for the onset of precocious puberty, agreeing with many others (10,11,36). This may occur due to breastfeeding also being a protective factor for obesity, and obesity itself could interfere with the onset and development of precocious puberty (37,38), which was also reaffirmed by our study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study also found breastfeeding as a possible protective factor for the onset of precocious puberty, agreeing with many others (10,11,36). This may occur due to breastfeeding also being a protective factor for obesity, and obesity itself could interfere with the onset and development of precocious puberty (37,38), which was also reaffirmed by our study.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, Kale et al (11) found that mixed-fed or predominantly breastfed girls showed later onset of breast development compared to formula fed girls, also, the duration of breastfeeding was directly associated with age at onset of breast development. Aghaee et al (36) in a study with 3,331 girls, found that those not breastfed were more likely to experience earlier thelarche and pubarche compared with girls who were breastfed ≥6 months. Similarly, a prospective observational study with boys and girls found an independent preventive association of breastfeeding for ≥6 months and early pubertal development, reinforcing our findings (10).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we examined the link between breastfeeding outcome and age at puberty onset in girls and boys. We found that, when considering breastfeeding alone, girls who were breastfed for at least six months experienced menarche at a slightly later age, as has been shown in other cohorts (Aghaee et al 2019). This effect attenuated, however, when body mass index at 10 years was included in the model.…”
Section: Discussionsupporting
confidence: 75%
“…Despite these findings, breastfeeding has recently been referred to as a critical independent factor in postponing sexual maturation in girls at higher risk of early puberty onset [ 89 ]. Authors observed an association between breastfeeding and thelarche at later age in 3331 mother–daughter pairs, after adjusting for maternal age at delivery, education level, and ethnicity, revealing that girls who were not breastfed were more likely to experience earlier thelarche than girls who were breastfed for six months [ 89 ]. In another study on 219 Korean children [ 10 ], authors found that subjects who were breastfed for over six months had lower odds of Tanner stage attainment ≥2 at nine years, compared with those who stopped breastfeeding before six months.…”
Section: Neonatal and Early Infancy Nutrition And Pubertymentioning
confidence: 99%